2011
DOI: 10.1074/jbc.m110.211078
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Vibrio cholerae Type II Secretome Reveals New Proteins, Including Three Related Serine Proteases

Abstract: The type II secretion (T2S) system is responsible for extracellular secretion of a broad range of proteins, including toxins and degradative enzymes that play important roles in the pathogenesis and life cycle of many Gram-negative bacteria. In Vibrio cholerae, the etiological agent of cholera, the T2S machinery transports cholera toxin, which induces profuse watery diarrhea, a hallmark of this life-threatening disease. Besides cholera toxin, four other proteins have been shown to be transported by the T2S mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
144
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(150 citation statements)
references
References 86 publications
6
144
0
Order By: Relevance
“…and human (i.e., Legionella pneumophila, Pseudomonas aeruginosa, Vibrio spp., and enterohemorrhagic Escherichia coli) pathogens (22). Among these pathogens, serine proteases have been identified as T2S substrates in Xanthomonas campestris and Vibrio cholerae (41)(42)(43). BLASTP analysis revealed that StmPr1 produced by strain K279a is most homologous with an annotated serine protease of Pseudomonas geniculata (69% identity), followed by annotated serine proteases of Xanthomonas sacchari (62% identity) and X. campestris (57% identity).…”
Section: Discussionmentioning
confidence: 99%
“…and human (i.e., Legionella pneumophila, Pseudomonas aeruginosa, Vibrio spp., and enterohemorrhagic Escherichia coli) pathogens (22). Among these pathogens, serine proteases have been identified as T2S substrates in Xanthomonas campestris and Vibrio cholerae (41)(42)(43). BLASTP analysis revealed that StmPr1 produced by strain K279a is most homologous with an annotated serine protease of Pseudomonas geniculata (69% identity), followed by annotated serine proteases of Xanthomonas sacchari (62% identity) and X. campestris (57% identity).…”
Section: Discussionmentioning
confidence: 99%
“…V. cholerae employs a T2SS to export at least 19 proteins, including its major virulence factor cholera toxin that is responsible for the profuse watery diarrhea that defines the disease. 74,75 The epsC-N operon and the pilD gene are required for production of the V. cholerae T2SS. 73,76 Aside from its export role, some studies have also implicated this T2SS in maintaining cell envelope integrity.…”
mentioning
confidence: 99%
“…V. cholera enters the body through an oral route of infection with contaminated water or food, and colonises the small intestine where it produces and secretes cholera toxin (Sikora, Zielke, Lawrence, Andrews, & Sandkvist, 2011). Its type II secretion system is responsible for extracellular secretion of a broad range of proteins including cholera toxin, hemagglutinin/protease, two aminopeptidases, and three serine proteases VesA, VesB, and VesC among others (Sikora et al, 2011). V. cholera secretes its own protease(s) that is/are responsible for cleaving (and thus activation) of cholera toxin (Booth, Boesmanfinkelstein, & Finkelstein, 1984).…”
Section: Food Pathogen-responsive Delivery Of Bioactivesmentioning
confidence: 99%
“…V. cholera secretes its own protease(s) that is/are responsible for cleaving (and thus activation) of cholera toxin (Booth, Boesmanfinkelstein, & Finkelstein, 1984). VesA, VesB, and VesC were just recently confirmed to have enzymatic activities, and knock-out strains indicated that VesA is the primary protease responsible for processing the A subunit of cholera toxin during in vitro growth of a V. cholerae strain (N16961) (Sikora et al, 2011), presumably indicating that VesA has a high degree of specificity. We suggest that nanocarriers containing crosslinking peptides having cleavage sites specific to either hemagglutinin/protease or VesA could be intelligent and effective strategies for the prevention and halting of this devastating disease, respectively.…”
Section: Food Pathogen-responsive Delivery Of Bioactivesmentioning
confidence: 99%